Derajat Ekspresi Fibroblast Activation Protein Pada Cancer-Associated Fibroblast Karsinoma Kolorektal - Vonny Amalia (Majalah Kedokteran Andalas, 2024)
Objective: to determine the degree of expression of Fibroblast Activation Protein in Cancer Associated Fibroblasts of colorectal carcinoma. Methods: descriptive study with a cross sectional research design. Using 36 paraffin blocks of CRC cases that met the inclusion criteria. FAP expression was assessed through immunohistochemical staining with anti-FAP and histopathological data were recorded in the form of depth invasion, degree of differentiation, lymphovascular invasion and lymph node metastatic status. Results: FAP in CAFs showed a high expression in most cases (52.8%). High-grade expression of FAP more common at T3-T4 depth of invasion, low-grade differentiation, CRC without lymphovascular invasion and CRC without lymph node metastases. Conclusion: there are variations in the expression of FAP as a marker of CAFs in colorectal carcinoma histopathology features.